2017
DOI: 10.1016/j.biopha.2016.12.101
|View full text |Cite
|
Sign up to set email alerts
|

Epiisopiloturine hydrochloride, an imidazole alkaloid isolated from Pilocarpus microphyllus leaves, protects against naproxen-induced gastrointestinal damage in rats

Abstract: Our data show that EPI protects against NAP-induced gastric and intestinal damage by reducing pro-inflammatory cytokines, reducing oxidative stress, and increasing GMBF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This mechanical test has an advantage over chemical tests, such as acetic acid‐induced writhing and the formalin tests, since it mimics clinical conditions associated with cutaneous hyperalgesia, such as neuropathic pain and osteoarthritis . Our data also suggest that EPI and EPIIS diminish the accumulation of neutrophils in the paw, as measured by the activity of the MPO enzyme in the tissue, corroborating previous studies have shown that these alkaloids inhibit the migration of cells to the inflammatory focus . This may be due to the blockade of the activation of neutrophils, as reported in the in vitro experiments because ROS generated by neutrophils can amplify their own recruitment and increase the severity of the inflammatory response by activation of transcription factors sensitive to changes in redox conditions, such as NF‐kB, which can control the expression of inflammatory cytokines and chemokines, thus favouring the recruitment of immune cells.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This mechanical test has an advantage over chemical tests, such as acetic acid‐induced writhing and the formalin tests, since it mimics clinical conditions associated with cutaneous hyperalgesia, such as neuropathic pain and osteoarthritis . Our data also suggest that EPI and EPIIS diminish the accumulation of neutrophils in the paw, as measured by the activity of the MPO enzyme in the tissue, corroborating previous studies have shown that these alkaloids inhibit the migration of cells to the inflammatory focus . This may be due to the blockade of the activation of neutrophils, as reported in the in vitro experiments because ROS generated by neutrophils can amplify their own recruitment and increase the severity of the inflammatory response by activation of transcription factors sensitive to changes in redox conditions, such as NF‐kB, which can control the expression of inflammatory cytokines and chemokines, thus favouring the recruitment of immune cells.…”
Section: Discussionsupporting
confidence: 90%
“…[45][46][47] Our data also suggest that EPI and EPIIS diminish the accumulation of neutrophils in the paw, as measured by the activity of the MPO enzyme in the tissue, corroborating previous studies have shown that these alkaloids inhibit the migration of cells to the inflammatory focus. [13][14][15] This may be due to the blockade of the activation of neutrophils, as reported in the in vitro experiments because ROS generated by neutrophils can amplify their own recruitment and increase the severity of the inflammatory response by activation of transcription factors sensitive to changes in redox conditions, such as NF-kB, which can control the expression of inflammatory cytokines and chemokines, thus favouring the recruitment of immune cells. However, we cannot exclude the possibility that EPI and EPIIS might also act directly on the neutrophils migration or exerting other anti-inflammatory mechanisms.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…mansoni [ 17 , 19 , 20 21 ]. Other biological functions have been described, including anti-inflammatory, anti-contraceptive [ 22 ], and gastro-protective effects [ 23 ]. The pharmacological action of epiisopilosine (EPIIS) and isopilosine (ISOP) against S .…”
Section: Introductionmentioning
confidence: 99%